2018
DOI: 10.1038/s41598-018-34703-1
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatremia in children with respiratory infections: a cross-sectional analysis of a cohort of 3938 patients

Abstract: Hyponatremia can be a life-threatening illness among hospitalized children. The aims of this study were to evaluate the incidence and risk factors of hyponatremia in 3938 children who were admitted to the Cheil General Hospital and Women’s Health Care Center with respiratory infections. Clinical data were collected, and multiplex RT-PCR analyses were done for various microorganisms. Hyponatremia was observed in 531 (13.5%) patients. The incidence of hyponatremia differed according to the respiratory tract infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 36 publications
1
26
2
Order By: Relevance
“…The marked increase in plasma IL-6 and TNF-α in IVIG-resistant infants compared with IVIG-responsive patients ( 31 , 32 ) may explain the significant hyponatremia in IVIG nonresponders. In our study, it was observed that hyponatremia and hypoalbuminemia correlated with an increase in acute phase reactants in IVIG-resistant patients ( 33 - 37 ).…”
Section: Discussionmentioning
confidence: 48%
“…The marked increase in plasma IL-6 and TNF-α in IVIG-resistant infants compared with IVIG-responsive patients ( 31 , 32 ) may explain the significant hyponatremia in IVIG nonresponders. In our study, it was observed that hyponatremia and hypoalbuminemia correlated with an increase in acute phase reactants in IVIG-resistant patients ( 33 - 37 ).…”
Section: Discussionmentioning
confidence: 48%
“…However, some observations suggest that hypernatremia is currently less common than hyponatremia [13]. The latter electrolyte abnormality has sometimes been documented also in children with further community-acquired diseases, such as lower respiratory tract infections [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…These findings are similar to results derived from present study(38).A retrospective cross sectional study done by Lavagno et.al in Cheil General Hospital and Women's Health Care Center, Seoul South Korea in 3938 children with respiratory infections between March, 2011, and February, 2014 is also consistent with present study. In this study, the duration of hospital stay in children with hyponatremia was 4.5±1.5 days and4.3±1.5 days in children with normal sodium ( p=0.020)(39).Another study was done by Kaneko et.al in Department of Pediatrics, Juntendo University Urayasu Hospital,Chiba, Japan. Medical record of 138 children was reviewed retrospectively in the year 2004.Objective of the study was to found the relation of hyponatremia and duration of hospital stay.…”
mentioning
confidence: 46%